Budgetary Punctuations: A Fiscal Management Perspective - Liu, Cheol (KDI School of Public Policy and Management, 2020)
Although the development of punctuated equilibrium theory (PET) makes broad reference to the bureaucratic procedures that regulate budgetary decision-making and makes reasonable assumptions about the influence that those procedures have on the dynamic of resource allocation, little is known about how the specific mechanisms work. This has led to a call to “understand the processes which lead to friction in greater detail” (Baumgartner et al, 2009). This research examines how budgetary output patterns are influenced by fiscal strategic choices made by governments. We find significant deviations of budgetary output patterns in capital projects, restricted funds, and entitlement spending, thus signifying the influence of fiscal management practices on resource allocation decisions. Furthermore, we empirically associate spending punctuation patterns with the growing democratic institutional development in Hong Kong. By examining legislative filibuster cases related to capital projects, we found evidence associating democratization with greater institutional frictions and consequently with larger budgetary output punctuations.
Keywords: Budgetary Punctuation; Fiscal Management; Fiscal Capacity Building